A Case in Which Good Control of Carcinomatous Serositis Was Achieved Using Chemotherapy Including Albumin-Bound Paclitaxel(Nab-PTX)for Advanced-Stage Pulmonary Adenocarcinoma Exhibiting Carcinomatous Pleurisy and Carcinomatous Pericarditis - Tsujita, Tomohiro; Kuronuma, Keiichiro; Hata, Norihiko (Gan to kagaku ryoho, 2018)
The subject was a 63-year-old man. The patient was transported by ambulance to the hospital because of dyspnea caused by carcinomatous pleurisy and carcinomatous pericarditis, after which pericardial drainage was performed; however, Staphylococcus aureus bacteremia arose as a complication. Adequate control of carcinomatous serositis was achieved usingchemotherapy, includingalbumin -bound paclitaxel(nab-PTX), which is a nanoparticle formulation bindinghuman serum albumin and paclitaxel, in combination with 1 course of antibiotics. For cancerous serositis cases, platinum combination chemotherapy usingnab -PTX is believed to be 1 treatment option in which good disease control can be expected along with bevacizumab, whose efficacy has already been confirmed.